Contributions of Interleukin‐33 and TSLP in a papain‐soaked contact lens‐induced mouse conjunctival inflammation model. Issue 4 (20th July 2017) - Sugita, Jobu; Asada, Yosuke; Ishida, Waka; Iwamoto, Satoshi; Sudo, Katsuko; Suto, Hajime; Matsunaga, Toru; Fukuda, Ken; Fukushima, Atsuki; Yokoi, Norihiko; Ohno, Tatsukuni; Azuma, Miyuki; et al.
Abstract: Introduction: Pathological changes of severe chronic allergic conjunctivitis are driven not only via acquired immunity but also via innate immunity. Type 2 immune response‐initiating cytokines may play some roles as innate immunity‐dependent components of the ocular surface inflammation. To investigate the involvement of type 2 immune response‐initiating cytokines in innate immunity‐dependent, papain‐induced conjunctival inflammation model using IL‐25‐, IL‐33‐, and TSLP receptor (TSLPR)‐knockout (KO) mice with reference to basophils and ILC2. Methods: Papain‐soaked contact lenses (papain‐CLs) were installed in the conjunctival sacs of C57BL/6‐IL‐25 KO, IL‐33 KO, TSLPR KO, Rag2 KO, Bas‐TRECK, and wild‐type mice and their eyes were sampled at day 5. The eosinophil and basophil infiltration in papain‐CL model was evaluated histologically and cytokine expression was examined. To clarify the roles of basophils and ILC2, basophil/ILC2‐depletion experiments were carried out. Results: Papain‐induced conjunctival inflammation exhibited eosinophil infiltration and upregulation of Th2 cytokine expression. Reduction of eosinophil and basophil infiltration and attenuated Th2 cytokine expression were observed in the papain‐CL model using IL‐33 KO and TSLPR KO mice. Depletion of basophils or ILC2s in the conjunctivae of the papain‐CL model reduced eosinophil infiltration. Conclusions: Innate immunity‐driven type 2 immune responses of the ocular surface are dependent on IL‐33, TSLP, basophils, and ILC2. These components may be possible therapeutic targets for refractory allergic keratoconjunctivitis. Abstract : In this study, we demonstrated the roles of IL‐33/TSLP in innate immunity dependent ocular surface inflammation using an innate immunity‐dependent, experimental mouse conjunctival inflammation model.